Teachers’ Role in Shaping Student Discipline in the Digital Era: A Case Study of SD 105438 Paya Lombang - Sukma Putri Aulia; Ismail Ismail (Journal of General Education and Humanities, 2025)
This research aims to investigate the role of elementary school teachers in instilling discipline in students amid the digital transformation occurring at SD 105438 Paya Lombang. Using a qualitative approach and case study method, data were collected through field observation, in-depth interviews with teachers and the school principal, as well as documentation of learning activities. The results show that teachers not only play a role as facilitators in the digital learning process but also as moral guides who instill values of discipline through an adaptive approach to technological developments. The use of digital tools such as learning applications, visual media, and communication platforms serves as a strategic means to build orderly and responsible learning routines. Nevertheless, this research also reveals various challenges faced, such as the limited digital literacy among teachers and students, as well as the lack of adequate technological infrastructure. Therefore, stronger collaboration is needed between schools, parents, and the community in creating a conducive, inclusive learning environment that is character-focused in the digital era.